Capital Inflows. - Elekdag, Selim (IMF Working Papers., 2009)
This paper examines the macroeconomic implications of, and policy responses to surges in private capital inflows across a large group of emerging and advanced economies. In particular, we identify 109 episodes of large net private capital inflows to 52 countries over 1987-2007. Episodes of large capital inflows are often associated with real exchange rate appreciations and deteriorating current account balances. More importantly, such episodes tend to be accompanied by an acceleration of GDP growth, but afterwards growth has often dropped significantly. A comprehensive assessment of various po.